PENERAPAN ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT PADA USAHA PENJUALAN KERIPIK TEMPE DENGAN PHP 5 DAN MYSQL - Winarti, Dwi (RC-INSTITUT, 2018)
CRM application program (Customer Relationship Management) Business Chips in Tempe Tino is a web-based program, wherein the application program is intended as an alternative option and is expected to replace the manual work processes.Within the scope of a highly competitive business nowadays Tempe Chips Enterprises Tino applying the concept of CRM is as a step to maintain good cooperative relationship with the customer.The purpose and function of the design of this CRM is to improve service to customers in order to maximize profits for the company. While the goal is for customers to be able to facilitate aspects of the transaction and to be able to submit complaints and dissatisfaction with the services obtained.